(untitled) (Mugda Medical College Journal, 2025)
Pentalogy of Fallot (PoF) is a rare form of congenital cyanotic heart disease. In the presence of the components of Tetralogy of Fallot (ToF), there is an additional defect in PoF; either atrial septal defect (ASD) or patent foramen ovale (PFO). Common Neurological complications of PoF include brain abscess and thrombosis. We present here a case of 18-year-old female with history of headache for 20 days. After her admission into the Department of Cardiology under Chattogram Medical College Hospital, Bangladesh, she was diagnosed as a case of POF; the fifth component was ASD. Her had history of illness suggestive of cyanotic spells since childhood. In the absence of any neurological deficit and cranial nerve involvement, fundoscopy revealed papilledema and sub hyaloid hemorrhage. Chest x-ray and echocardiography revealed typical features of ToF, with additional ASD. CT scan of brain showed subarachnoid hemorrhage. Conservative management was given after consultation with the Department of Neurology of the same hospital. Unlike ToF, which has been extensively described, PoF is less represented in the literature. Therefore, we present this case as an academic interest. Mugda Med Coll J. 2024; 7(2): 135-138